Variations in kinematic variables and performance in the tennis serve according to age and skill level - Hernández-Davó, J. L.; Moreno, F. J.; Sanz-Rivas, D.; Hernández-Davó, H.; Coves, Á.; Caballero, C. (International Journal of Performance Analysis in Sport, 2019)
To analyse the influence of age and skill level on tennis serve performance, 99 male participants took part in a study of maximum effort serves to a target (50 x 50 cm) in the add service box. Participants were divided into two skill level groups (elite and recreational) and three age groups (under 12 years old [U12], under 16 years old [U16] and +18). During testing, kinematic data were recorded and serving performance (accuracy and speed) was measured. A single-way analysis of variance (ANOVA) was used to analyse the differences for kinematic and performance variables between the six groups. Correlation analysis was performed to establish the relationships between kinematics variables and serve performance. Results highlighted the influence of both age and skill level on performance (speed and accuracy), as well as on kinematics (hand, arm, hip peak velocities) of the tennis serve. The spatial position of the hand in respect to the hip in the moments previous to ball impact in the medio-lateral, and the vertical axes was significantly correlated with serving performance in all the age groups. These results suggested that an increased range of motion of shoulder external rotation and wrist flexion, as well as higher velocities of shoulder internal rotation and elbow extension should be developed to increase tennis serve speed.